Dad's new clothes - John, Louise; Latimer, Miriam (Wayland London, 2010)
Mum and Poppy are taking Dad shopping but he does NOT like shopping! Dad's New Clothes is part of the Start Reading: Going Shopping series, four books at Red Band 2 of the Start Reading programme.